Sustainable Development Framework for Local Governance - Josef T. Yap; Michael R. Cabalfin (Philippine Institute for Development Studies (PIDS), 2008)
Over the past sixty years, the concept of development has expanded from economic growth and investment, to poverty reduction, human development, sustainable development, and more recently to institutional development. There has also been a fresh look at industrial policy and the role of the nonfarm economy. These aspects of development are not only important in their own right but are very much interrelated. National development experience shows the importance of investment and infrastructure to growth; the significance of growth, infrastructure, and human development to poverty reduction; the contribution of growth and human development to sustainable development; the effect of nonfarm incomes to growth, poverty reduction, and inequality; and the importance of institutions to growth. Local development experience also reveals the interrelatedness of the different development aspects: the importance of investment, infrastructure, and human capital to growth and poverty reduction; the role of health to human capital; the significance of human capital to poverty and inequality; the value of human development, institutions, and good governance to sustainable development; the importance of human capital to enterprise development; and in turn of enterprise development to investment and therefore growth as well as to poverty reduction; the contribution of nonfarm incomes to growth and poverty reduction; and the importance of governance to poverty reduction and human development.
Keywords: 330; economic growth; poverty; sustainable development; inequality; enterprise development; human development; local governance; regional development; nonfarm economy; industry clustering; institutional development; Regionalentwicklung; Armut; Soziale Ungleichheit; Regionales Cluster; Institutioneller Wandel; Entwicklungspolitik; Philippinen